Qualitative research design : an interactive approach - Maxwell, Joseph Alex (Thousand Oaks, Calif. : Sage Publications, 2005)
"Qualitative Research Design: An Interactive Approach, Second Edition provides researchers and students a user-friendly, step-by-step guide to planning qualitative research. A bestseller in its first edition, this invaluable book presents an innovative approach to the components of design and how they interact with each other. The text presents a clear strategy for creating coherent and workable relationships among these design components and highlights key design issues. Based on a course the author taught for seven years at the Harvard Graduate School of Education, the work is written in an informal, jargon-free style and incorporates many examples and hands-on exercises."--P. [4] of cover
A model for qualitative research design -- Goals : why are you doing this study? -- Conceptual framework : what do you think is going on? -- Research questions : what do you want to understand? -- Methods : what will you actually do? -- Validity : how might you be wrong? -- Research proposals : presenting and justifying a qualitative study -- Appendix : an example of a qualitative proposal
Includes bibliographical references (p. 159-166) and index
Keywords: Research -- Methodology